ZnO nanoparticles inhibit the activity of Porphyromonas gingivalis and Actinomyces naeslundii and promote the mineralization of the cementum - Jingyu Wang; Lele Du; Yingmei Fu; Peidong Jiang; Xiumei Wang (BMC, 2019)
Abstract Background Zinc oxide nanoparticles (ZnONPs) have been widely studied as bactericidal reagents. However, it is still challenging to use ZnONPs as a root canal sealant to eliminate infecting microorganisms in the root canal system. This study aimed at understanding the antibacterial and biofilm effects of ZnONPs in the infected root canal and their effect on cell function. Methods This study aimed to develop a better understanding of the antibacterial effects of ZnONPs in the infected root canal and their effect on cell function. Experiments were performed in two stages; the first stage included inhibition zone tests and the minimum inhibitory concentration (MIC) test, which were performed to examine the antibacterial activity of ZnONPs against Porphyromonas gingivalis (P. gingivalis) and Actinomyces Naeslundii (A. naeslundii) bacteria in vitro. ZnONPs were further evaluated for their biocompatibility using normal mouse NIH3T3 and OCCM-30 cells by the cell-based MTT assay. In addition, the influence of ZnONPs on matrix metalloproteinases in NIH3T3 cells and their inhibiting factors (Mmp13 and Timp1) were measured using the real-time PCR technique and western blot method. Results The MIC of ZnONPs against P. gingivalis and A. naeslundii were confirmed to be 10 μg/mL and 40 μg/mL, respectively. The MTT assay showed that ZnONPs were nontoxic. The RT-PCR and western blotting results showed that Mmp13 was downregulated and Timp1 expression was increased. Meanwhile, ZnONPs were shown to increase the expression of the OCCM-30 osteogenesis-related factors Bsp and Runx2. Finally, there was no significant change in the morphology of NIH3T3 and OCCM-30 cells after the addition of different concentrations of ZnONPs for different periods of time. Conclusion ZnONPs have excellent antibacterial activity against P. gingivalis and A. naeslundii and have low cell cytotoxicity in vitro.